2014
DOI: 10.1007/s00340-014-5820-3
|View full text |Cite|
|
Sign up to set email alerts
|

Vortex and anti-vortex compositions of exact elegant Laguerre–Gaussian vector beams

Abstract: Reformulation of conventional beam definitions into their bidirectional versions and use of Hertz potentials make beam fields exact vector solutions to Maxwell's equations. This procedure is applied to higherorder elegant Laguerre-Gaussian beams of transverse magnetic and transverse electric polarization. Their vortex and anti-vortex co-axial compositions of equal and opposite topological charges are given in a closed analytic form. Polarization components of the composed beams are specified by their radial an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…12 of the PV in both rotational cases, we could infer the magnetic energy ε −1 | H z | 2 from the measurable electric energy μ −1 | E z | 2 . This idea can be traced back to the concept of the Stokes parameters [ 17 ]. In addition, because we have solved the Maxwell's equation self-consistently by use of the functions , , and in Equations 3–6, not only the dipoles but also all the higher-order multipoles have been taken into account [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 of the PV in both rotational cases, we could infer the magnetic energy ε −1 | H z | 2 from the measurable electric energy μ −1 | E z | 2 . This idea can be traced back to the concept of the Stokes parameters [ 17 ]. In addition, because we have solved the Maxwell's equation self-consistently by use of the functions , , and in Equations 3–6, not only the dipoles but also all the higher-order multipoles have been taken into account [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, TE and TM waves in co-rotations have the same azimuthal mode index, thereby referring to the same AM. Instead, we concentrate here on the TE and TM waves in counter-rotations, thus referring to the opposite azimuthal mode indices [ 15 , 17 ]. By duplexing, an interference is implied, which is also present in the interactions among multiple beams [ 3 4 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The idea to use superposition of uniformly polarized beams to create nonuniformly polarized waves was first proposed by Hajnal [48,49]. This fruitful concept was further developed to construct many specific polarization structures in optical beams [50,[64][65][66][67][68][69][70]. Particularly, Gori [50] showed that the field of a superposed vortices with the opposite topological charges can be linearly polarized at any point, but the polarization direction changes with the angular coordinate.…”
Section: Vector Topologies In Paraxial Electromagnetic Wavesmentioning
confidence: 99%
“…The idea to use superposition of four uniformly linearly polarized vortex beams to create nonuniformly polarized waves was first proposed by F. Gori [41]. It was further developed, with little variations, to construct more general complex polarization structures [62,[64][65][66][67][68][69][70]. Following this technique, we consider the circularly polarized field with modulating functions Eqs.…”
Section: Vector Topologies In Paraxial Electromagnetic Wavesmentioning
confidence: 99%